The novel hyaluronic acid granular hydrogel attenuates osteoarthritis progression by inhibiting the TLR‐2/NF‐κB signaling pathway through suppressing cellular senescence - Chen Zhang; Zhengxiang Cheng; Yuanyuan Zhou; Ziyi Yu; Hongyu Mai; Changhao Xu; Jing Zhang; Jiali Wang (Wiley, 2023)
Abstract In patients with mild osteoarthritis (OA), two to four monthly injections are required for 6 months due to the degradation of hyaluronic acid (HA) by peroxidative cleavage and hyaluronidase. However, frequent injections may lead to local infection and also cause inconvenience to patients during the COVID‐19 pandemic. Herein, we developed a novel HA granular hydrogel (n‐HA) with improved degradation resistance. The chemical structure, injectable capability, morphology, rheological properties, biodegradability, and cytocompatibility of the n‐HA were investigated. In addition, the effects of the n‐HA on the senescence‐associated inflammatory responses were studied via flow cytometry, cytochemical staining, Real time quantitative polymerase chain reaction (RT‐qPCR), and western blot analysis. Importantly, the treatment outcome of the n‐HA with one single injection relative to the commercial HA product with four consecutive injections within one treatment course in an OA mouse model underwent anterior cruciate ligament transection (ACLT) was systematically evaluated. Our developed n‐HA exhibited a perfect unification of high crosslink density, good injectability, excellent resistance to enzymatic hydrolysis, satisfactory biocompatibility, and anti‐inflammatory responses through a series of in vitro studies. Compared to the commercial HA product with four consecutive injections, a single injection of n‐HA contributed to equivalent treatment outcomes in an OA mouse model in terms of histological analysis, radiographic, immunohistological, and molecular analysis results. Furthermore, the amelioration effect of the n‐HA on OA development was partially ascribed to the attenuation of chondrocyte senescence, thereby leading to inhibition of TLR‐2 expression and then blockade of NF‐κB activation. Collectively, the n‐HA may be a promising therapeutic alternative to current commercial HA products for OA treatment.